The competitiveness assessmant model a case study of OGP Technical Services Sdn. Bhd.-Based on the internal organizational perspectives / Kamarul Noor'ain Khairi - Khairi, Kamarul Noor'ain (2004)
The Competitiveness Assessment Model is a simple tool that allows for analysis beyond the known quantifiable data into creative synthesis that contains eight main categories that play a role in the competitiveness of any enterprise. The eight components are:- (1) Organizational Structure, (2) Global Presence, (3) Products And Methodologies, (4) Operations, (5) Research And Development, (6) Market Image, (7) Growth Strategy and (8) Management. Each category has five subcomponents addressing specific area of concern within the category. This model has been adopt and modified in order to obtain a greater and accurate results that meet with the objectives and hypotheses of the study. The several aspect of the modification can be seen in the data analysis section whereby the ranking is basically based on the level of employees' perceptions towards the contribution of the 8 components to the high competitive advantages of the company. Each of the finding will be placing within a 'wagon-wheel-matrix". When completed, a judgment call can be made about the overall competitiveness of the company (OGP Technical Services Sdn. Bhd.).